Social Justice Mathematics and Public Health Equity: A Systematic Review of Quantitative Literacy in Health Decision-Making - Terungwa James Age (GHMJ (Global Health Management Journal), 2026)
Background: Public health decision-making increasingly requires individuals to interpret numerical information such as risks, probabilities, treatment benefits, and epidemiological trends. However, disparities in quantitative literacy may contribute to inequitable health outcomes and reduced participation in informed decision-making. Despite growing interest in health literacy and equity, systematic reviews have examined health numeracy, risk communication, and health literacy; however, limited research has specifically examined the role of social justice mathematics in strengthening equitable health decision-making. Aim: This systematic review examined how quantitative literacy and health numeracy influence health decision-making, explored how numeracy disparities contribute to public health inequities, and assessed how social justice mathematics may support equitable engagement with health information. Methods: Guided by PRISMA 2020, a systematic search of Scopus, Web of Science, PubMed, and ERIC was conducted for studies published between 2000 and 2025. Following screening and eligibility assessment, 50 studies were included in the final synthesis. Two independent reviewers conducted article screening and quality appraisal, with disagreements resolved through discussion and consensus. A narrative synthesis approach was adopted due to methodological heterogeneity across studies. Findings: The review found that limited numeracy contributed to misinterpretation of health risks, reduced screening participation, difficulties in treatment decision-making, and lower engagement in preventive healthcare, particularly among socioeconomically disadvantaged populations. The findings further showed that social justice mathematics may strengthen critical interpretation of health data, improve engagement with public health issues, and support awareness of structural inequities. However, empirical evidence directly linking social justice mathematics interventions to measurable health outcomes remains limited. Conclusion: Quantitative literacy is a critical determinant of equitable health decision-making. Public health systems should adopt numeracy-sensitive communication strategies, while education systems should integrate socially responsive quantitative literacy and authentic health data into mathematics curricula to strengthen informed participation and reduce health inequities.